Discourse Analysis of Mistress in Youtube Video “Deddy Corbuzier dan Mulan Jameela – A Deep Conversation” - Juniati, Vitri; Dwiningtyas, S.Sos, MA, Dr. Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Woman has always been the one to blame in infidelity. The woman is also the one who got stigmas from society as the mistress. When a woman who got stigmas trying to speak, it showed her fight against those stigmas through her voice. This research’s aim is to know about how woman’s voice presents to against the society's dominant mindset such as the label and stigma that given to woman. This descriptive-qualitative research uses feminism discourse analysis by Sara Mills to analyze dialog, video and comments in four elements which are character, fragmentation, focalization, and schemata. The outcome of this research showed that woman still cannot get away from stigma and label that given to her, even though she is already trying to speak up against it. Mulan Jameela, as a woman who is inferior to society, shows she fights through her voice but didn’t make it. She missed the chance to answer society’s judges towards her through this video because she is still in the same perspective as the commenters; how to be a good mother, how to be a supportive wife, her denial on the blame that given to her in infidelity, also the perspective she used to see how her relationship with Ahmad Dhani –her husband. Mulan Jameela is stuck in society dominant mindsets that make her to be the mistress who is indeed the only one to blame in infidelity. At the end, the fight that Mulan Jameela tried to do with her voice against society, didn’t make her out of the topics and the mindset of dominant thinking which society is believed in.